A Grounded Low-Cost UHF RFID Tag Antenna for Long-Range Metallic and Non-Metallic objects Applications - M. E. A. Lakhal; M. A. Ennasar; M. EL Khamlichi; M. Aznabet; O. El Mrabet; M. Khalladi (Advanced Electromagnetics)
This paper presents an ultra-high frequency (UHF) RFID tag antenna designed to operate within the American frequency band (902-928 MHz) and perform reliably when placed on metallic objects. The design features a microstrip dipole antenna with symmetrical U-shaped stubs, capacitively coupled to a metallic patch and grounded with a substrate. The antenna is printed on a low-cost FR4 substrate (1.6 mm thickness), with overall dimensions of 90 mm × 95 mm × 1.6 mm. The antenna achieves a realized gain of -4.8 dB, with a free-space reading range of approximately 7 m, which increases to 10.5 m when placed on a 50 cm× 30 cm metallic plate. The key of this design lies in its use of capacitive coupling, which eliminates the need for metallic vias or shorting walls. This simplification not only facilitates mass production but also enhances the design’s performance, offering a superior reading range on larger metallic objects compared to other designs reported in the literature that provide a small reading range. The proposed antenna offers a robust solution for RFID applications on both metallic and non-metallic objects.